A Giant Cavernous Hemangioma of the Left Atrioventricular Groove - Chengming Fan; Changming Tan; Demiao Kong; Jinfu Yang; Shuwen Yuan; Sijie Wu (Case Reports in Pediatrics)
A 10-year-old Chinese female diagnosed with an asymptomatic giant cardiac cavernous hemangioma was reported. The patient originally tended to observation because this unusual cardiac tumoral mass was discovered incidentally during routine health examination of transthoracic echocardiography. Over 5 years of follow-up, the mass had enlarged obviously, and the patient visited our outpatient clinic and was prone to excision. Subsequently, a total resection surgery of the tumor was performed, and the tumor was found to be located on the left atrioventricular groove with complete packing membrane. The patient was discharged on postoperative day 4 and remains asymptomatic on last follow-up.